HPLC Method Development and Validation for Simultaneous Analysis of Diclofenac Sodium and Rabeprazole Sodium - A. A. Heda; D. D. Gadade; J. M. Kathiriya; P. K. Puranik (E-Journal of Chemistry)
A stable, simple, rapid, precise, accurate RP-HPLC method for simultaneous analysis of diclofenac sodium and rabeprazole sodium was developed and validated as per ICH guidelines without need of any internal standard. Separation was carried out using C8 column with triethyl amine buffer (pH 5): acetonitrile (50:50 v/v) as mobile phase with flow rate 2 mL min-1. The detection was carried out at 284 nm. The parameters studied were retention time, linearity and range, accuracy, precision, detection limit, quantitation limit and bench top stability. The proposed method can be used for simultaneous estimation of diclofenac sodium and rabeprazole sodium in bulk drugs and pharmaceutical dosage forms.